Lower crustal thickening drives active uplift in Northern Tibet - Liu, Shaozhuo; Xu, Xiwei; Nocquet, Jean-Mathieu; Chen, Guihua; Tan, Xibin; Jónsson, Sigurjón; Klinger, Yann (Earth and planetary science letters, 2025)
■Continuous GPS measurements reveal 1–2 mm/yr of uplift on the East Kunlun Shan with respect to the Qaidam Basin.■Hydrological loading, erosional unloading, glacial isostatic adjustment cannot explain the GPS-observed uplift.■Unrealistically large reverse-slip rate of 1.5–2.5 mm/yr is required to explain the GPS-observed uplift.■Mantle processes cannot drive the sharp uplift gradient observed by GPS.■Lower crustal thickening likely drives the GPS-observed uplift. Mountains in collisional orogens generally grow as crustal rocks are advected over low-angle thrust faults, suggesting a close relationship between tectonic uplift and upper crustal shortening. For example, the Himalayas, hosting large-scale thrust fault systems, undergoes ∼15–20 mm/year shortening and concomitant ∼5 mm/year active uplift. However, geodetic observations reveal an active uplift of 1–2 mm/year across the East Kunlun Shan mountain range, the northern margin of the Tibetan Plateau, where no active thrust fault has been identified. This active uplift is too fast to be explained by the limited horizontal shortening of at most 1.0 ± 0.2 mm/year. After quantifying and correcting for contributions arising from erosion, (de)glaciation, and recent earthquakes, the uplift rate across the East Kunlun Shan still amounts to 1.0 ± 0.5 mm/year. Our simulations show that mantle processes cannot explain the GPS-observed uplift. We find that lower crustal thickening, rather than upper crustal shortening alone, drives the ongoing uplift across the East Kunlun Shan, hence challenging our current views on mountain range dynamics.